Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 462: 85



Work Step by Step

$x^{2}-3xy-4y^{2}$ ... Searching for two factors of $ac=-4$ whose sum is $b=-3,$ we find$\qquad 1$ and $-4.$ Rewrite the middle term and factor in pairs: $=x^{2}+xy-4xy-4y^{2}=$ $=x(x+y)-4y(x+y)$ = $(x+y)(x-4y)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.